ВИКЛИКИ ПІД ЧАС РЕФОРМУВАННЯ СИСТЕМ ОХОРОНИ ЗДОРОВ’Я - Гущук, Р. І.; Олексюк, Н. Є.; Седляр, Н. В.; Редзель, Г. П.; Надейко, А. М. (Українські медичні вісті, 2023)
ВИКЛИКИ ПІД ЧАС РЕФОРМУВАННЯ СИСТЕМ ОХОРОНИ ЗДОРОВ’Я